Haemophilus influenzae type b disease in the era of conjugate vaccines: critical factors for successful eradication. (2nd October 2020) - Slack, Mary; Esposito, Susanna; Haas, Hervé; Mihalyi, Attila; Nissen, Michael; Mukherjee, Piyali; Harrington, Lauriane
ABSTRACT: Introduction: Prior to implementation of Haemophilus influenzae type b (Hib)-conjugate vaccination programs in the 1990s, Hib was the commonest cause of bacterial meningitis in children aged <5 years. While the burden of all Hib disease has significantly decreased in the post-vaccination era, Hib still accounted for >29, 000 deaths worldwide in children aged <5 years in 2015. Areas covered: We reviewed literature data on the most widely used Hib vaccines and vaccination strategies which led to the global prevention and control of Hib disease and aim to highlight important factors for continued disease control and elimination in the future. Expert commentary: More than 90% of countries worldwide have implemented Hib-conjugate vaccination in their national immunization programs. Vaccines containing Hib polyribosylribitol phosphate (PRP) conjugated with tetanus toxoid (Hib-TT) are the most commonly used. Neisseria meningitidis outer membrane protein complex of PRP (Hib-OMP) is also used. Although the kinetics of the immune response varies with Hib vaccine and schedule used, high control of Hib disease was observed in all settings/scenarios. Further improving global Hib vaccination coverage may result in disease elimination. Plain language summary: What is the context? Haemophilus influenzae is causing a variety of diseases, from otitis media and sinusitis to invasive disease (e.g. meningitis and pneumonia). H. influenzae type b (Hib) was the most common cause of bacterial meningitis in children <5 years of age, and especially among <2-year-olds. Even with appropriate treatment, up to 40% of children with bacterial meningitis can suffer permanent disabilities and up to 5% will die. The development of vaccines to protect against Hib disease has started in the late 1970s and has culminated with the licensure of 4 Hib conjugate vaccines, of which 2 are currently widely used. What is new? In this review, we gathered evidence on the different Hib vaccines and vaccination strategies that have contributed to the global prevention and control of Hib disease. The review indicates: the incidence of Hib disease has decreased considerably due to the introduction of Hib vaccines in national immunization programs worldwide. However, Hib disease is not yet completely eradicated. the vaccines currently used offer protection against Hib over long periods of time. carriage of the pathogen by healthy individuals seem to be less frequent, but data are still needed to fully evaluate the impact of vaccination. other H. influenzae types are now more frequent. Why is this important? Despite the huge success of Hib vaccination, continuous surveillance is needed to anticipate potential re-emergences and devise the best strategies for prevention and control of disease. Hib vaccination should be considered in the few countries who have not yet implemented it, to decrease associated morbidity and mortality.